2020
DOI: 10.1515/htmp-2020-0034
|View full text |Cite
|
Sign up to set email alerts
|

Study on the structure activity relationship of the crystal MOF-5 synthesis, thermal stability and N2 adsorption property

Abstract: AbstractThe parallel flow drop solvothermal method was utilized to synthesize the crystal of MOF-5 by taking the molar ratio of the metal ions to the organic ligands of 2:1 at 140C, and the reaction time at 12 hours. Meanwhile, the structure and properties of MOF-5 were characterized by the X-ray diffraction (XRD), scanning electron microscope (SEM), thermogravimetric analysis (TGA) and fourier transform infrared spectroscopy (FTIR). SEM analysis shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The second weight loss observed in the temperature range of 293.16−384.31 °C was 21.35%, which might be due to the decomposition of polymeric PAN from the organic framework and some guest molecules from the open metal sites in Co-MOF-5 fibers. 55,56 Finally, a notable mass loss was observed in the temperature range of 384.31 to 1000 °C with an estimated mass loss of 43.39%, due to the structural collapse of the organic framework. These results have shown that the Co-MOF-5 fiber remains stable at a maximum temperature of 462.26 °C, and the degree of purity was also observed to be very high.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The second weight loss observed in the temperature range of 293.16−384.31 °C was 21.35%, which might be due to the decomposition of polymeric PAN from the organic framework and some guest molecules from the open metal sites in Co-MOF-5 fibers. 55,56 Finally, a notable mass loss was observed in the temperature range of 384.31 to 1000 °C with an estimated mass loss of 43.39%, due to the structural collapse of the organic framework. These results have shown that the Co-MOF-5 fiber remains stable at a maximum temperature of 462.26 °C, and the degree of purity was also observed to be very high.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Then, 8.62 g of 2-methylimidazole was dissolved in 30 mL of distilled water, and the volume of the solution was measured using a graduated cylinder (38 mL). The two solutions were mixed rapidly under magnetic stirring at 353 K. At 1,2,4,6,8,10,15,20,30,40,50, and 60 min, approximately 1 mL of the mixture was withdrawn from the mother liquor and quickly filtered, and 0.5 mL of the filtrate was collected. All of the filtrates were dissolved in 2 mL of 2 M HCl and further diluted to 100 mL, and the Co and Zn concentrations in the dilute solution were then measured by ICP-AES.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The metal species in MOFs can be highly dispersed even when the metal content is as high as 30 wt %. MOF-5, a typical MOF comprising a cluster of zinc oxide connected with a 1,4-benzenedicarboxylate (BDC) linker, contains 34 wt % Zn, and the Zn species are unaggregated, as evident from X-ray diffraction (XRD) and other studies . In contrast, a chabazite -type zincosilicate zeolite with Zn species embedded in the zeolitic framework contained impurities on the external surface, where the bulk Si/Zn ratio was 16.7 (i.e., Zn content ≈ 6 wt %) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized efficiency is plotted as a function of exhaust pressure at different cooling temperatures. It is important to realize that the highest heating temperatures for MOF-5 and HKUST-1 are limited to their decomposition temperatures, which are generally measured as 623 K for both adsorbents [44,45]. Therefore, the heating temperature limit is set at 600 K for these two adsorbents in both the thermodynamic and dynamic models, whereas there is no such limit for Saran carbon.…”
Section: Effect Of the Exhaust Pressurementioning
confidence: 99%